2019
DOI: 10.1007/s10811-019-01993-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of bacterial pathogens on edible macroalgae in coastal waters

Abstract: In the Northeast USA, the aquaculture of macroalgae is a rapidly growing industry. Within this region, there are no established regulations for farm siting or methods of pathogen detection on macroalgae cultivated or harvested for human consumption. Bacterial pathogens from natural and anthropogenic sources may persist in coastal waters and can potentially contaminate macroalgae. During the winter growing season, sugar kelp Saccharina latissima and adjacent water were sampled from three sites of kelp aquacultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 74 publications
0
10
0
2
Order By: Relevance
“…This finding appears to be treatment specific and unrelated to total mesophilic counts (Figure 8), which closely resembled LAB counts in both level and trend. The elevated coliform level in the 75% SK treatment likely due to the slower rate of acidification in the higher inclusion level SK formulations, but calls for further investigation to assess the potential survival of foodborne pathogens such as shigatoxigenic E. coli , which has been detected on freshly harvested SK (Barberi, Byron, Burkholder, St. Gelais, & Williams, 2020) and closely related Salmonella . Fungi were found only sporadically on any of the samples tested during this study (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…This finding appears to be treatment specific and unrelated to total mesophilic counts (Figure 8), which closely resembled LAB counts in both level and trend. The elevated coliform level in the 75% SK treatment likely due to the slower rate of acidification in the higher inclusion level SK formulations, but calls for further investigation to assess the potential survival of foodborne pathogens such as shigatoxigenic E. coli , which has been detected on freshly harvested SK (Barberi, Byron, Burkholder, St. Gelais, & Williams, 2020) and closely related Salmonella . Fungi were found only sporadically on any of the samples tested during this study (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Pathogens from environmental and anthropogenic sources may persist in coastal waters and can potentially cause contamination. Research on bacterial pathogen contamination of seaweeds is limited, and literature is scarce for some areas e.g., US coastal waters [74] while more literature is found from other parts of the world. Sugar kelp Saccharina latissima and adjacent water were sampled from three sites of seaweed aquaculture located in adjacent bays of Maine, USA, during the winter growing season [74].…”
Section: Escherichia Coli Salmonella Spp Listeria Monocytogenes Staph...mentioning
confidence: 99%
“…This fact may be due to the initial bacterial load of the macroalgal samples as this may vary depending on the sampling site and also sampling procedures and pore-treatments applied to the biomass prior to their inclusion into food formulations. Recently, Barberi et al [ 145 ] reported the presence of foodborne pathogens, such as S. Typhimurium , V. parahaemolyticus and enterohemorrhagic E. coli O157:H7, on kelp samples analyzed using molecular methods. The authors concluded that although the bacterial counts in the seaweeds were generally low, there is a risk for consumers associated with the presence of foodborne pathogens [ 145 ].…”
Section: Incorporation Of Antimicrobial Compounds From Macroalgae In Food Matricesmentioning
confidence: 99%
“…Recently, Barberi et al [ 145 ] reported the presence of foodborne pathogens, such as S. Typhimurium , V. parahaemolyticus and enterohemorrhagic E. coli O157:H7, on kelp samples analyzed using molecular methods. The authors concluded that although the bacterial counts in the seaweeds were generally low, there is a risk for consumers associated with the presence of foodborne pathogens [ 145 ]. Thus, the pre-treatments of the macroalgal biomass, such as cleaning, drying and extraction procedures used to obtain macroalgal ingredients, may influence considerably the initial microbial loads of meat and other food products formulated using macroalgae and/or macroalgal ingredients.…”
Section: Incorporation Of Antimicrobial Compounds From Macroalgae In Food Matricesmentioning
confidence: 99%